2000
DOI: 10.1046/j.1439-0396.2000.00286.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting ascorbic acid biosynthesis in chickens. I. Adaptation of an assay and the effect of age, sex and food deprivation

Abstract: Summary The objective of this study was to adapt an assay to measure L‐gulonolactone oxidase (GLO) activity, the final step in ascorbate synthesis, in chickens and use the procedure to study the effect of gender, age, and food deprivation. To adapt a procedure used for mammalian tissues the kinetic constants were estimated using chicken kidney and assay conditions optimized in terms of storage of tissue and homogeneity of distribution. A series of experiments were conducted using the standardized assay with in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 22 publications
3
19
2
Order By: Relevance
“…Poultry are renal synthesizers of ascorbic acid (AsA) (Grollman and Lehninger, 1957) and diets are not normally fortified. The kinetic constants of chicken l-gulonolactone oxidase (GLO) and time course changes in activity (Hooper et al, 2000) are similar to results reported for rats (Chatterjee and McKee, 1965) and gender differences were similar to those reported for dogs and rabbits with activity lower in males. A common assumption is that biosynthesis may be inhibited or turnover increased in the presence of stressors and supplementation may be beneficial (Coates, 1984;Hornig et al, 1984;Peebles and Brake, 1985;Gross, 1988;Kutlu and Forbes, 1993;McKee and Harrison, 1995;Amakye-Anim et al, 2000).…”
Section: Introductionsupporting
confidence: 82%
See 2 more Smart Citations
“…Poultry are renal synthesizers of ascorbic acid (AsA) (Grollman and Lehninger, 1957) and diets are not normally fortified. The kinetic constants of chicken l-gulonolactone oxidase (GLO) and time course changes in activity (Hooper et al, 2000) are similar to results reported for rats (Chatterjee and McKee, 1965) and gender differences were similar to those reported for dogs and rabbits with activity lower in males. A common assumption is that biosynthesis may be inhibited or turnover increased in the presence of stressors and supplementation may be beneficial (Coates, 1984;Hornig et al, 1984;Peebles and Brake, 1985;Gross, 1988;Kutlu and Forbes, 1993;McKee and Harrison, 1995;Amakye-Anim et al, 2000).…”
Section: Introductionsupporting
confidence: 82%
“…Tissue samples were processed and assayed within 3 weeks storage at −20 °C. Renal GLO (EC 1.1.3.8) activity was assayed within 2 weeks of tissue collection ( Hooper et al, 2000). A blank was run with each sample to correct for endogenous AsA in the renal homogenate.…”
Section: Biochemical Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The samples were maintained in ice, plasma separated by centrifugation and ascorbic acid determined within 4 h of collection (Hooper et al, 2000). The birds were killed by exposure to carbon dioxide and the distal portion of the left kidney, the adrenal glands and liver were sampled, wrapped in aluminium foil, kept in a plastic bag immersed in slush ice and later stored at À20 C. Liver samples and adrenal glands were homogenised in 10 volumes of 5% cold trichloroacetic acid for 10 s using a Polytron homogeniser.…”
Section: Biochemical Measurementsmentioning
confidence: 99%
“…The homogenate was centrifuged at 12 000 g and 4 C for 2 min and the supernatant used to measure ascorbic acid (Creel et al, 2001). The liver and adrenal gland samples were processed within 4 weeks of storage at À20 C. Renal L-gulonolactone oxidase [EC 1.1.3.8] activity was assayed within 2 weeks of tissue collection (Hooper et al, 2000). A blank was performed with each sample to correct for endogenous ascorbic acid.…”
Section: Biochemical Measurementsmentioning
confidence: 99%